Evaluation of Alvardo score in diagnosis of acute appendicitis - Mokati, Uday Kiran; Rao, L. Hari Prasada; Durgesh, N. Siva; Avinash, P.; Lakshmi, K. Baby; Prasad, K. S. S. V. R. A.; Teja, V. Viswa; Bhargavi, P.; Deepika, B. Anu; Krishna, P. Rama (International Surgery Journal, 2017)
Background: Acute appendicitis is a common cause of abdominal pain for which a prompt diagnosis is rewarded by a marked decrease in morbidity and mortality. Right Iliac fossa pain is the hallmark of acute appendicitis until proven otherwise. Decision making in a case of acute appendicitis may be difficult, especially for junior surgeons. Hence, we aimed at analysing the Alvarado Score in patients with right iliac fossa pain. Methods: A prospective study involving 120 patients with right iliac fossa pain attending KIMS casualty during May 2015- April 2016 were included in the study. Results: The least was in the age group of 56 to 65 years (2%). Out of 120 patients, 84 were males (70%) and 36 were female (30%). The male to female ratio was 1:0.4. Patients with Alvarado score 7-9 (Group I) includes 60 male and 26 females (71% of total study group). Alvarado score 5-6 (Group II) includes 17 males,19 female (22% of total study group). Alvarado score 1-4 (Group III) includes 7 males, and 1 female (7% of total study group). In patients of Group I, among 60 males, 51 were confirmed with acute appendicitis. Among 26 females, 19 were confirmed with acute appendicitis, with a positive appendicectomy rate of 81.3% and negative appendicectomy rate 19.7%. The numbers of patients were highest in the age group 15 to 25 years (38%) followed by 36 to 45 years (30%). Conclusions: The Modified Alvarado scoring system was found to be highly effective in the diagnosis of the acute appendicitis in men and can be widely used to avoid expensive time consuming and non-readily available additional investigations. However, this system was not very effective in women. Therefore, ultra sound examination of abdomen and pelvis and diagnostic laparoscopy are also advised to minimize the high false negative rate in women which excludes common pelvic pathology that mimic clinically acute appendicitis.